2015
DOI: 10.2147/dddt.s86370
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cubosomes as a targeted and sustained transdermal delivery system for capsaicin

Abstract: Phytantriol- and glycerol monooleate-based cubosomes were produced and characterized as a targeted and sustained transdermal delivery system for capsaicin. The cubosomes were prepared by emulsification and homogenization of phytantriol (F1), glycerol monooleate (F2), and poloxamer dispersions, characterized for morphology and particle size distribution by transmission electron microscope and photon correlation spectroscopy. Their Im3m crystallographic space group was confirmed by small-angle X-ray scattering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…The samples were then tested in vivo on mice and showed no signs of irritation, indicating that cubosomes may be a viable alternative to currently available commercial creams. [139] The majority of ocular problems and illnesses are treated with eye drops. However, key problems include corneal permeability, retention times and low solubility of some drugs.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…The samples were then tested in vivo on mice and showed no signs of irritation, indicating that cubosomes may be a viable alternative to currently available commercial creams. [139] The majority of ocular problems and illnesses are treated with eye drops. However, key problems include corneal permeability, retention times and low solubility of some drugs.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…Recently, it has been envisioned that cubosomes can act as an ideal drug delivery system for drugs with poor loading and permeability for the treatment of topical fungal infections 12 .Moreover,ithas been reported that cubosomes can serve as a potential skin retentive system [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Unique structure of cubosomes can incorporate wide varieties of drugs (hydrophilic, lipophilic and amphiphilic) with high pay load owing to their high internal surface area (400 m 2 /g) 12,[16][17] . Various investigations have also indicated the sustained and prolonged drug delivery properties of cubosomes 14,18 . Moreover, similarities between the bicontinuous structures formed in human skin layers and those comprising cubic phases 19 , offering the promise of better skin retention and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Yet capsaicin is actually irritant to human skin producing a burning sensation [2], and because of its high degree of first-pass metabolism in gastric intestinal track and short half-life by intravenous administration (7.06 min) [3, 4], transdermal delivery system seems to be more advantageous for capsaicin. In our previous research, we chose cataplasm [5], cubic phase gel [6, 7], and cubosome [8, 9] as transdermal delivery system providing the sustained release for capsaicin.…”
Section: Introductionmentioning
confidence: 99%